Abundance of the life stages of three Calanus species and Metridia longa during Polarstern cruise ARK-XXVI/3 (PS78, TRANSARK) - Kosobokova, Ksenia Nikolaevna; Hirche, Hans-Juergen; Hopcroft, Russell R; Ershova, Elizaveta A; Cornils, Astrid (In: Cornils, Astrid; Hirche, Hans-Juergen (2021): Collection of zooplankton abundance data from the Arctic Ocean during POLARSTERN cruises [dataset publication series]. Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, PANGAEA, https://doi.org/10.1594/PANGAEA.926084, 2023)
Abundances of the life stages of the three Calanus species (Calanus finmarchicus, Calanus glacialis and Calanus hyperboreus) and Metridia longa was calculated in the Arctic Ocean during Polarstern cruise ARK-XXVI/3. Samples were taken with the Multinet maxi (Hydrobios, Kiel), which is equipped with nine nets (mesh size: 150 µm).
Keywords: Arctic Ocean; Calanus finmarchicus; Calanus glacialis; Calanus hyperboreus; Copepoda; Metridia longa